Troponin I – a comprehensive review of its function, structure, evolution, and role in muscle diseases - Dongju Han; Younghyun Lim; Soah Lee; Seong-il Eyun (Animal Cells and Systems)
The troponin complex is a critical component of thin filaments and plays an essential role in the calcium-mediated regulation of contraction and relaxation in striated muscles, including both cardiac and skeletal muscle. Troponin I, a subunit of this complex, inhibits actomyosin interactions during muscle relaxation. Its function is finely tuned by posttranslational modifications, particularly phosphorylation, which influence calcium sensitivity and actin affinity, thus impacting muscle contraction. Mutations in troponin I are closely associated with various human diseases. Specifically, several mutations in cardiac troponin I have been linked to cardiomyopathies, such as hypertrophic, dilated, and restrictive cardiomyopathies, which affect heart contractility and calcium handling. In this review, we explore the multifaceted aspects of troponin I, including its structure, functional role in muscle contraction, evolution, and the complex interactions between posttranslational modifications and genetic mutations that alter its function and contribute to disease progression.